Anmeldelser - Rosenberg, Herbert (Danish Yearbook of Musicology, 1980)
Review of: Carl Nielsen: Maskarade. Comic Opera in 3 acts. Libretto by Vilhelm Andersen after the play by Ludvig Holberg. Dansk Musik Antologi 032/4. Ib Hansen, Gurli Plesner, Tonny Landy, Mogens Schmidt Johansen, Christian Sørensen, Gert Bastian, Edith Brodersen, Tove Hyldgaard, Jørgen Klint, Ove Verner Hansen, Aage Haugland, Peter Bach-Mortensen, Michael W. Hansen, Hans Christian Andersen, Birger Brandt, Ingeborg Junghans, Betty Breum, Kirsten Buhl Møller, Kim von Binzer, Kaare Hansen, Jørgen Hviid, Niels Erik Flen, Karl Gustav Andersson. Danish Radio Symphony Orchestra and Chorus, conducted by John Frandsen. Unicorn RHS 350/2.